Faktor Yang Berpengaruh Terhadap Perilaku Preventif Penyebaran Covid-19 - Febrina Secsaria Handini; Oda Debora (Jurnal Keperawatan Malang, 2022)
Background: WHO declared that COVID-19 is a global pandemic and Indonesian government has designated it as biological disaster in the form of a disease outbreak that required an integrated response through several steps. These countermeasures and preventions require the involvement of all components of society, including people of young and productive age. This preventive effort during the COVID-19 pandemic is a new habit that must be carried out by all circles of society as a form of the adaptation process to the new situation, namely the COVID-19 pandemic situation. To examine changes in people's behavior towards the COVID-19 pandemic, researchers used the PRECEDE-PROCEED model as a conceptual framework in this study. Purpose: This study aim was to determine the factors that influenced the preventive behavior of Covid 19 spread in adolescents and productive ages. Methods: This research is a cross-sectional quantitative research, 63 respondents was taken for each adolescent and productive age. Sampling technique was simple random sampling. The data was collected with 12 questionnaires which were valid and reliable. Result: There was a significant relationship with a positive direction between Predisposing Factors, Enabling Factors and Reinforcing Factors on Covid-19 Prevention Behavior. The dominant factor which influenced the preventive behavior to prevent the spread of Covid 19 in Pandansari was the reinforcing factor where the component in it was accessibility to health services. Conclusion: The role of health workers is very important to prevent the spread of Corona virus infection and improve the community health status.